2007
DOI: 10.1682/jrrd.2007.02.0029
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of group versus individual hearing aid visits

Abstract: Abstract-Demand for hearing aid services in the VeteransHealth Administration increased over 300% from 1996 to 2005, challenging the delivery of timely, high-quality care. Using group visits may help meet these needs, but whether this approach would still provide high-quality rehabilitation is unclear. This study determined whether group visits worsen hearing aid outcomes. It included a retrospective observational cohort in veterans seeking hearing aids at the Department of Veterans Affairs Puget Sound Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Similar to fi ndings on improved compliance following group consultations on the management of chronic diseases, it was shown that a group consultation on hearing aids led to better adherence to wearing hearing aids (Collins et al, 2007). A group consultation can be seen as an occasion where an individual can gather necessary information from both the audiology professional and people who are either potential or existing hearing-aid users.…”
Section: Acclimatization and Positive Supportmentioning
confidence: 69%
See 4 more Smart Citations
“…Similar to fi ndings on improved compliance following group consultations on the management of chronic diseases, it was shown that a group consultation on hearing aids led to better adherence to wearing hearing aids (Collins et al, 2007). A group consultation can be seen as an occasion where an individual can gather necessary information from both the audiology professional and people who are either potential or existing hearing-aid users.…”
Section: Acclimatization and Positive Supportmentioning
confidence: 69%
“…A summary of these studies was drawn up, listing the author and year of publication, country, study design, and data collection method, aim, subjects, sample size, instruments used, hearing-aid (Hartley et al, 2010;Ham et al, 2014;Hickson et al, 2014), and only two in Asia (Chang et al, 2009;Mizutari et al, 2013). The majority of the studies were cross-sectional studies, three were cohort studies (Collins et al, 2007;Fischer et al, 2011;Mizutari et al, 2013), two were randomized controlled trials (Yueh et al, 2001;Saunders et al, 2009), and one was a longitudinal study (Humes et al, 2002). The age of the participants of these studies ranged from 50 to 97.…”
Section: Data Extractionmentioning
confidence: 99%
See 3 more Smart Citations